Congenital Pyloric Atresia: Experience with a Series of 11 Cases and Collective Review - Gungi Raghavendra Prasad; J V Subba Rao; Firdous Fatima; Fariha Anjum (Wolters Kluwer Medknow Publications, 2021)
Introduction: Pyloric atresia is a rare cause of congenital gastric outlet obstruction. It is often associated with epidermolysis bullosa (EB). Rarity and experience with 11 cases are the reason for this publication. Aims and Objectives: The aim and objective of this study is to present our experience of 11 cases of congenital pyloric atresia and correlate with available literature. Materials and Methods: This was retrospective cohort of 11 cases correlative comparative study. Data of all the 11 cases from 1982 to 2019 were collected, reviewed, and analyzed. The parameters studied included age, gender, antenatal diagnosis, postnatal diagnosis, preoperative management, intraoperative findings, postoperative course outcome, associated anomalies, and any genetic studies if done. All these parameters were compared with published data. Results: There were 11 cases in the present series with six boys and five girls. Most of them presented at varying periods from birth to day 1 of life. Eight cases of type 1 pyloric atresia, two cases of type 2 pyloric atresia, and one case of type 3 pyloric atresia constituted the cohort. Five out of 11 cases were associated with EB. Two out of six cases with isolated pyloric atresia and four out of five cases with EB died. Discussion: Congenital pyloric atresia may be isolated or associated with EB. Three varieties of pyloric atresia were described. Association with EB increases the mortality. Conclusions: Review and analysis of 11 cases of pyloric atresia compared with published literature is being reported.